Prophet Yousuf (3Ydjg GdSdGe (Band the king's dreams - SaniyasnainKhan (china goodwordbooks, 2024)
This enchantingly illustrated board book delightfully introduces to the children the inspiring life and teachings of the Prophet Zakariya.